Stress-Related Disorders - Ovuga, Emilio (IntechOpen, 2022)
This book presents a comprehensive overview of traumatic stress. Chapters address such topics as biomarkers in traumatic stress, the role of microglia activation, proliferation, and neuro-inflammation in the genesis of mental disorders and pain, the role of anger in the genesis and maintenance of hypertension, the role of anger and imagery in the maintenance of stress-related disorders, the role of oxidative stress in the etiology and maintenance of cardiovascular diseases, the mental health impacts of the COVID-19 pandemic, and much more.